208k views
1 vote
Rationalize the denominator in each expression. That is, rewrite the expression so that there is a rational expression in the denominator a)((x-9)/√(x-9))b)((x-9)/(√x+3))

User Miketucker
by
8.3k points

1 Answer

4 votes

Answer:

explanations: we multiply with a rational surd

(x-9)*√(x+9)/(√(x-9)*√(x+9)

=(x-9)√(x+9)/


x {}^(2) - 9

B.( x-9)/√x+3 =( x-9)*(√x-3)/(√x+3)*(√x-3)

= (x-9)*(√x-3)/x-9

=√x-3

User Firman
by
8.4k points

Related questions

1 answer
5 votes
129k views
1 answer
5 votes
51.9k views
1 answer
0 votes
51.9k views